2011
DOI: 10.1002/jctb.2754
|View full text |Cite
|
Sign up to set email alerts
|

Removal of ampicillin sodium in solution using activated carbon adsorption integrated with H2O2 oxidation

Abstract: BACKGROUND: The removal of antibiotic ampicillin sodium using H 2 O 2 and modified granular activated carbon (GAC) is discussed. Two types of modified activated carbons were used in experiment to catalyze ·OH production from H 2 O 2 . One was modified with base (NaOH; called B-GAC), the other was modified with Fe(NO 3 ) 3 (Fe-GAC) and the nominal Fe metal loading was 5 wt%. In the experiment, pH, contact time, dosage of activated carbon and H 2 O 2 and initial concentration of ampicillin sodium were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…For the molar ratios of 1, 10, 50 and 100, 3-CP removal after 6 h was 84, 91, 78 and 76 %, and the k 2 values were as follows: 2.430, 3.275, 1.522 and 1.223 g mmol -1 h -1 . These results agree with the earlier studies, which reported that an excessive concentration of hydrogen peroxide decreases the degradation efficiency of the organic compounds including ampicillin [17] and paraquat [14] by AC/H 2 O 2 . It may be due to the fact that some of the organic compounds and oxidation by-products were quickly removed by the adsorption and did not react with the H 2 O 2 , so they did not consume H 2 O 2 .…”
Section: Effect Of H 2 O 2 Concentrationsupporting
confidence: 93%
See 2 more Smart Citations
“…For the molar ratios of 1, 10, 50 and 100, 3-CP removal after 6 h was 84, 91, 78 and 76 %, and the k 2 values were as follows: 2.430, 3.275, 1.522 and 1.223 g mmol -1 h -1 . These results agree with the earlier studies, which reported that an excessive concentration of hydrogen peroxide decreases the degradation efficiency of the organic compounds including ampicillin [17] and paraquat [14] by AC/H 2 O 2 . It may be due to the fact that some of the organic compounds and oxidation by-products were quickly removed by the adsorption and did not react with the H 2 O 2 , so they did not consume H 2 O 2 .…”
Section: Effect Of H 2 O 2 Concentrationsupporting
confidence: 93%
“…It may be due to the fact that some of the organic compounds and oxidation by-products were quickly removed by the adsorption and did not react with the H 2 O 2 , so they did not consume H 2 O 2 . Also, the more resistant by-products generated during the oxidation process could only be removed by the activated carbon, and as a result, a further increase of the H 2 O 2 concentration did not improve the removal efficiency [17]. Dhaouadi and Adhoum [14] reported that the decrease in the oxidation efficiency observed at high H 2 O 2 dosages may be due to its scavenging effect towards the hydroxyl radicals according to the following reactions:…”
Section: Effect Of H 2 O 2 Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations of ampicillin sorption on activated carbons have suggested that the surface interactions were mainly of electrostatic nature [29]. Most carbons have points of zero charge (PZC) of ca.…”
Section: Removal Studiesmentioning
confidence: 99%
“…Pharmaceutical treatment technologies including ozonation, photo‐catalytic degradation and other advanced oxidation processes (AOPs) have been investigated by many researchers . Recently ferrate (VI) has been studied comprehensively, as it could be an alternative to the other AOPs for the removal of pharmaceutical residuals .…”
Section: Introductionmentioning
confidence: 99%